2022
DOI: 10.1111/avsc.12683
|View full text |Cite
|
Sign up to set email alerts
|

Summer grazing by three livestock species at moderate intensity enhances primary productivity and drives community divergence in a semi‐arid steppe

Abstract: Aims:The general effects of grazing by large herbivores on plant species composition and productivity are well known. Meanwhile, how different livestock species affect community structure is not fully understood. In northern China, livestock species composition is changing rapidly and hence, it is imperative to understand the resulting effects on grassland productivity and composition.Location: Xilingol, Inner Mongolia, China. Methods:We studied how grazing by three major livestock species affects typical step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…Precipitation in the usually dry early stage of the plant growing season promotes plant growth and biomass more than in the late stage (Hossain & Beierkuhnlein, 2018). The increase in plant AGB over the three‐year period in the studied grassland is driven by the precipitation, not by the additive effects of management over the period, as revealed by a partial correlation analysis of AGB with precipitation and “year” (representing the vegetation succession or additive effects) for the same experimental grassland (Li et al, 2022). The effects of precipitation on community attributes differ for the grassland in different grazing seasons (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…Precipitation in the usually dry early stage of the plant growing season promotes plant growth and biomass more than in the late stage (Hossain & Beierkuhnlein, 2018). The increase in plant AGB over the three‐year period in the studied grassland is driven by the precipitation, not by the additive effects of management over the period, as revealed by a partial correlation analysis of AGB with precipitation and “year” (representing the vegetation succession or additive effects) for the same experimental grassland (Li et al, 2022). The effects of precipitation on community attributes differ for the grassland in different grazing seasons (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…The copyright holder for this this version posted December 24, 2022. ; https://doi.org/10.1101/2022.12.24.521851 doi: bioRxiv preprint Grassland vegetation is widely used for livestock grazing to support secondary production in drylands. Numerous studies have revealed the impact of livestock grazing on plant community composition mediated by selective herbivory, depending on the livestock species (Díaz et al, 2007;Li et al, 2022;Sasaki et al, 2008a). The grazing impacts on plant species richness and community composition differed according to changes in water availability among the sites.…”
Section: Introductionmentioning
confidence: 99%